Reduction of order
(t)d^2y/dt^2 - (t+1)dy/dy + y = t^2
y1(t) = e^t y2(t) = t + 1
I have to do this is 2 different methods the first method was using variation of parameters which I could do but then when it came to using reduction of order I kept getting stuck half way.
The first thing i did was let y = ue^t then i differentiated and subbed back intothe equation then it was u absent which let me use p = du/dt and dp/dt = d^2u/dt^2 then i got P = tc/(e^t -t) where c is a constant then i couldnt integrate that to find u.
Rewrite your equation in this form
Originally Posted by CookieC